Валовий внутрішній продукт України в контексті глобальних викликів - Дернова, І. А.; Боровик, Т. М.; Данилевська, Л. С.; Dernova, I. A.; Borovyk, T. M.; Danylevska, L. S. (Видавництво Львівської політехніки, 2023)
Проаналізовано динаміку ВВП України з огляду на соціальні та політичні виклики останніх років. Для порівняльного зіставлення використано номінальний та реальний ВВП. Проведений аналіз дав змогу зробити висновок про синхронність зміни номінального та реального ВВП України впродовж 2018–2022 рр. Розглянуто залежність обсягу ВВП України від таких факторів, як експорт, імпорт, прямі інвестиції, інфляція, рівень безробіття та розміру мінімальної заробітної плати. З цією метою застосовано кореляційно-регресійний аналіз, що дозволив визначити найвагоміші фактори впливу серед обраних макроекономічних показників. Також автори визначають основні проблеми, з якими зіткнулася національна економіка протягом останніх років, та наголошують на необхідності вжиття ефективних заходів для їх нівелювання.

The article analyses the dynamics of Ukraine‘s GDP in the light of social and political challenges of recent years. Ukraine‘s GDP dynamics were negatively affected by the COVID-19 pandemic and the ongoing full-scale russian invasion. The factors that caused a slowdown in economic growth in most regions of the world are also outlined: large-scale quarantine measures, supply chain disruptions, the abolition of fiscal stimulus for economic development, and tight monetary policies of central banks in developed countries. The dynamics of nominal and real GDP for the period 2007–2022 are analyzed. The analysis allowed to conclude that the changes in nominal and real GDP of Ukraine in 2018–2022 are synchronized, which is confirmed by the calculated correlation coefficient. The article examines the dependence of Ukraine‘s GDP on such factors as exports, imports, direct investments, inflation, unemployment and the minimum wage. For this purpose, the authors used correlation and regression analysis to identify the most important factors of influence among the selected macroeconomic indicators. The authors also identify the main problems faced by the national economy in recent years and emphasize the need to take effective measures to mitigate them. The purpose of the research is to provide a comparative analysis of the condition of the national economy through the analysis of macroeconomic indicators, specifically gross domestic product in different periods: in the context of global challenges caused by the pandemic and military aggression of the Russian Federation. To achieve this goal, a series of tasks are required: to analyse the level of GDP and assess the impact of the COVID-19 pandemic on the Ukrainian economy; to identify the main challenges faced by the Ukrainian economy under martial law; to analyse changes in various indicators that describe the economic, technological, investment and social aspects of the country; to study measures taken by the government and determine the prospects for economic development in the context of post-pandemic and post-war recovery. The research methods: are comparison, explanation, abstraction, empirical analysis and synthesis, a combined method of similarity and divergence.
Gross domestic product of Ukraine in the context of global challenges
Keywords: валовий внутрішній продукт; обсяг ВВП; номінальний ВВП; реальний ВВП; експорт; імпорт; інвестиції; інфляція; рівень безробіття; gross domestic product; GDP volume; nominal GDP; real GDP; exports; imports; investments; inflation; unemployment rate; 330.55